Implementation of heterodyning effect for monitoring the health of adhesively bonded and fastened composite joints - ÜNAL, MUHAMMET (ELSEVIER SCI LTD, 2018)
Composite materials are a preferred choice when high strength/weight ratio and resistance to corrosion are needed. For assembly, composite parts are joined by using adhesives and/or fasteners. Due to the increased use of composites, there is a need for reliable and affordable structural health monitoring (SHM) methods for the detection of weakened bonds and loosened fasteners. Heterodyne effect may be utilized for the evaluation of debonded area when the linear characteristics of the system changes to nonlinear as a result of light contact in the bonding zone and this nonlinear system responds to appropriate bitonal excitations with new frequencies. Nonlinear elastic wave spectroscopy (NEWS) methods are using the same concept although they are limited to the combination of a high and a low frequency. Heterodyne method allows the engineers to have control over the new output frequencies as indicators of nonlinearity in the target structure. In this study, implementation of the heterodyne method is proposed for identification of the debonded region and evaluation of the compressive forces applied to facing plates. The proposed SHM method proved to be effective in both scenarios. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Structural health monitoring; SHM; Composite; Heterodyne method; Debonding; Delamination; ELASTIC-WAVE SPECTROSCOPY; RESONANT ULTRASOUND SPECTROSCOPY; DAMAGE IDENTIFICATION; DEFECT DETECTION; INTER-LAMINAR; TIME-REVERSAL; LOCALIZATION; SIMULATION